Productivity Measurements for Accounting Functions - SUWARDY, Themin (Institutional Knowledge at Singapore Management University, 2012)
The finance department is under pressure to enhance its own value contribution to the business, deliver high quality information and maintain effective controls. It is subject to the same continuing internal demands to reduce the cost of its own operations. To be more effi cient, be more productive. But many finance departments are in a quandary. They are unsure how to demonstrate whether they are delivering real value to the business and to what extent they meet best practice standards for world-class finance departments.